"Book of the Open Lithuania" - the first ten years - Zinkevičienė, Julija; Misiūnas, Remigijus (Knygotyra, 2003)
The Publishing program of the Lithuanian Open Foundation (Soros Foundation) has been working for more than ten years. The specialists of the Faculties of Communication and Philosophy had done a research of the activity of the Publishing program in 2001–2002. One of the tasks of this research was to see how the activity of the Publishing program influenced the publishing in Lithuania. LOF has been supporting publishing of the risky (from commercial viewpoint) literature, such as philosophy, political science, cultural science and others. This is very important in such small market as Lithuania. The books, supported by LOF, are included into one big series – "Book of the Open Lithuania". These books make a substantial part of humanitarian and social science literature, published in Lithuania. Publishing program has been working on the base of „leaving" strategy – LOF is creating or supporting structures, which are going to continue the started work. The forms and mechanisms of support for publishing houses were changed constantly, depending on economical and other conditions in Lithuania. The publishing houses, which worked with LOF, became stronger in financial aspect and they obtained experience of working in academic literature market. The support for publishing of the academic literature is still very important in Lithuania and the biggest problem is the replacement of LOF when the foundation will finish its activity in Lithuania.